Improved cytoreductive potential of plateletapheresis in the treatment of thrombocythemia: a single center study - Balint, Bela; Pavlović, Mirjana; Ostojić, Gordana; Vučetić, Dušan; Todorović, Milena (Vojnosanitetski pregled, 2021)
No Abstract